A Case of Resembling Hemolytic Uremic Syndrome Caused by Escherichia fergusonii in an Immunocompetent Adult - Hwang, Soyoon; Chang, Hyun-Ha; Bae, Sohyun; Kim, Yu Kyung; Kim, Jungmin (Chonnam medical journal, 2022)
KCI Citation Count: 0